(untitled) (2017)
Central Argentina has numerous saline lakes sustained by groundwater sources and rainfall. These lakes are temporary and experience significant changes in water level and salinity, depending on wet and dry climate cycles. This study aims to investigate the scarcely known dynamics of environmental and zooplankton parameters during the drying phase of one of these lakes. Monthly samples were taken from December 2 012to July 2 013 in the Ojo de Agua Uriburu lake, previous to its drying. At the beginning of the study, the lake’s depth was 0.7 m and its salinity was 16.65 g/L, later, in July, its depth decreased to 0.06 m and its salinity increased to 92.9 g/L. Zooplankton species richness was low (three crustaceans and three rotifers), with Boeckella poopoensis and Moina eugeniae dominating in the system. Maximum density and biomass were attainedby the two dominant species in April (318.5 ind/L and 3 029.1 g /L dry weight; and 242.4 ind/L and 1 530.4 g/L dry weight, for B. poopoensis and M. eugeniae, respectively), and no correlation was found between these parameters and salinity. Maximum average body lengths for both species were observed in the last months of sampling (M. eugeniae: 1 020 84.2 m and B. poopoensis: 1 348.8 89.0 m). At this point of the study, neither juvenile nor larval stages were found. The increase in average body size is, arguably, the result of increased salinity in the system through a negativeeffect on reproduction. Because this lake reached hypersalinity, its ecological dynamics are unique among those of other temporary, saline lakes that dried in central Argentina. Similar studies on other temporary ecosystems are needed to increase the information on these little known ecological aspects.